Faktor-Faktor yang Mempengaruhi Penerapan Aplikasi Audit Tool and Linked Archive System (ATLAS) (Studi Kasus pada Kantor Akuntan Publik di Kota Pekanbaru) - Naiya Aulia Putri; Rama Gita Suci; Wira Ramashar (Jurnal Ekonomi, Akutansi dan Manajemen Nusantara, 2026)
This study aims to analyze factors influencing the adoption of the Audit Tool and Linked Archive System (ATLAS) application at Public Accounting Firms (KAP) in Pekanbaru City. The factors examined include auditor competence, perceived ease of use, perceived usefulness, auditor trust, system quality, and information quality. This study employed a quantitative approach with a survey method, distributing questionnaires to 55 external auditors working at KAPs in Pekanbaru City who had used the ATLAS application. The sampling technique used was purposive sampling. Data were analyzed using multiple linear regression with SPSS software. The results showed that, both partially and simultaneously, auditor competence, perceived ease of use, perceived usefulness, auditor trust, system quality, and information quality had a positive and significant influence on the adoption of the ATLAS application. The coefficient of determination indicates that these variables explain 66.8% of the ATLAS application adoption, while the remainder is influenced by factors outside this study. This research is expected to provide theoretical contributions to the development of the literature on audit technology adoption and provide practical considerations for regulators and Public Accounting Firms in improving the effectiveness of ATLAS application implementation.